The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1167/iovs.15-17892
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Optic Disc Tilt in the Progression of Primary Open-Angle Glaucoma

Abstract: PURPOSE.To evaluate the effect of optic disc tilt on the progression of glaucoma in myopic glaucomatous eyes.METHODS. The disc tilt ratio was estimated on disc photographs. Glaucomatous progression was determined either by stereoscopic optic disc/retinal nerve fiber layer photographs or serial visual field data. All participants were categorized into two groups according to tilt ratio (nontilted [<1.3] or tilted [ ‡1.3]). Kaplan-Meier life-table analysis was used to compare the survival experiences (time to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
1
35
1
1
Order By: Relevance
“…A previous study reported a smaller probability of glaucoma progression in the eyes with tilted disc compared to those with non-tilted disc [7]. The result of the present study appears to be contradictive to the results of the previous study; however, the discrepancy might be explained by many differences between two studies, mostly in methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study reported a smaller probability of glaucoma progression in the eyes with tilted disc compared to those with non-tilted disc [7]. The result of the present study appears to be contradictive to the results of the previous study; however, the discrepancy might be explained by many differences between two studies, mostly in methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…A greater extent and faster rate of VF progression were observed in eyes with non-tilted discs than in eyes with tilted discs. This finding was in accordance with a previous report from our group 24. A study by Han et al 23 found that eyes with an inferiorly tilted disc tended to show no VF progression after terminating VF progression at the region associated with the optic disc tilt; this suggested that optic disc tilt may act as a positive prognostic factor after a certain level of damage has been reached.…”
Section: Discussionsupporting
confidence: 92%
“…3,17 The optic disc center was determined to be the point where the long and short axes of the disc crossed, as described in previous studies. [18][19][20][21][22] The two aforementioned glaucoma specialists independently assessed the presence and angular circumference of CMvD; any disagreements between these two specialists were resolved by a third adjudicator (M.S.K.). The average values from the two measurements were used in the analysis to minimize interobserver variation.…”
Section: B-zone Peripapillary Atrophy and Choroidal Microvascular Dromentioning
confidence: 99%